Identification of risk factors associated with umbilical hernia in under 5 children: A hospital based study - Amin, Shayla; Islam, Nazrul; Quddush, ASM Ruhul; kamruzzaman, -; Badruzzaman, -; Parvin, Sabiha; Sultana, Faria (Community Based Medical Journal, 2018)
Umbilical hernia is one of the most commonly encountered abnormalities in early months of infancy and childhood. Though umbilical hernia is a common benign condition which resolves spontaneously during first 5 years of life, it may be a great concern to the parents and other caregivers. Therefore, the high index of suspicion, prompt recognition and thorough understanding of common factors are necessary to ensure their correction and convince the parents to treat. A hospital based cross sectional observational study was conducted in the paediatrics unit of Community Based Medical College & Hospital from March 2013 to September 2013 to determine the factors associated with umbilical hernia. A total of 160 cases of umbilical hernia admitted in paediatrics unit and outpatient department of Community Based Medical College & Hospital were enrolled in the study. Necessary information were collected by detailed history taking, clinical examination and close follow up of the hospital course, using pre-designed questionnaire. Among 160 patients, malnutrition were observed in 21.8% , severe malnutrition was the most common abnormality (45%) followed by moderate malnutrition 28.05%, mild malnutrition 28.05%. Low birth weight were found to have 21.3%, among medical condition, excessive crying were 18.7%, chronic cough were 18.7%, constipation were 17.5%, positive family history 1.9%. Malnutrition and low birth weight are more common association of umbilical hernia.Malnutrition has great impact on developing umbilical hernia. Chronic cough, excessive crying, constipation more or less equally responsible. So early identification of risk factors and proper management and close monitoring are important to reduce the risk of developing umbilical hernia. CBMJ 2018 July: Vol. 07 No. 02 P: 04-08